Endometrial polyps: optimization of anti-inflammatory therapy - Т. Ф Татарчук; Н. В. Косей; О. В. Занько; Т. І. Юско (Publishing House TRILIST, 2018)
The frequency of hyperproliferative pathology of endometrium is about 60-70% in the structure of gynecological pathology of postmenopausal women. Endometrial polyps are a fairly frequent gynecological pathology for women of all ages, but the overwhelming majority of them are diagnosed at the age of 40-60 years. According to a number of studies, the frequency of endometrial polyps is 39.2-69.3%, and the endometrial polyposis occupies the first place in the structure of intrauterine pathology in postmenopausal. Given the important role of inflammation in the etiology of endometrial polyps and the risk of infectious complications in the postoperative period, there is a need for a comprehensive approach to the examination and treatment of this pathology. To date, ultrasound diagnostics and hysteroscopy are considered the standard for diagnosing endometrial polyps. However, the use of hysteroscopic technique in postmenopausal patients has a number of limitations, which are primarily associated with the possible occurrence of anesthetic and surgical complications. With age in the body, women experience atrophic changes in the genital area, which are often the cause of the formation of stenosis and obliteration of the cervical canal, which increases the risk of injury during his burying and can lead to the formation of a «false» course and even perforation of the uterus. This causes a more complicated postoperative period, which is characterized by a pain syndrome, the presence of subfebrile, hematometry, etc. In addition, given the growth in postmenopausal frequency of extragenital pathology and metabolic syndrome, during the surgical interventions and in the postoperative period, the risk of thrombotic complications increases. The article presents the substantiation of the expediency of conducting anti-inflammatory therapy in the postoperative period in postmenopausal patients after hystero-rectoscopic removal of polyps. The risk of complications of inflammatory nature after hysteroscopy is quite high and is 3-10%. The expediency of using the combined treatment regimen of endometrial polyps in this patient population using the enzyme complex Distreptaza®, which reduces the severity and duration of the pain syndrome, reduces the risk of developing subfebrile and formation of hematometry.